Surface-Tailored Zein Nanoparticles: Strategies and Applications - Ahmed M. Abdelsalam; Ahmed Somaida; Abdallah Mohamed Ayoub; Fahd M. Alsharif; Eduard Preis; Matthias Wojcik; Udo Bakowsky (MDPI AG, 2021)
Plant-derived proteins have emerged as leading candidates in several drug and food delivery applications in diverse pharmaceutical designs. Zein is considered one of the primary plant proteins obtained from maize, and is well known for its biocompatibility and safety in biomedical fields. The ability of zein to carry various pharmaceutically active substances (PAS) position it as a valuable contender for several in vitro and in vivo applications. The unique structure and possibility of surface covering with distinct coating shells or even surface chemical modifications have enabled zein utilization in active targeted and site-specific drug delivery. This work summarizes up-to-date studies on zein formulation technology based on its structural features. Additionally, the multiple applications of zein, including drug delivery, cellular imaging, and tissue engineering, are discussed with a focus on zein-based active targeted delivery systems and antigenic response to its potential in vivo applicability.